2019
DOI: 10.1177/1479164119843094
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of circulating microvesicles in coronary artery disease patients with type 2 diabetes and albuminuria: Effects of exercise training

Abstract: Objective:Circulating microvesicles, released from activated/apoptotic cells, are involved in vascular complications and may be looked upon as biomarkers. Albuminuria is characteristic of disease progression in type 2 diabetes mellitus. We aimed to investigate quantitative and qualitative differences of circulating microvesicles in type 2 diabetes mellitus with and without albuminuria and whether 12-month exercise training influenced expression of circulating microvesicles.Methods:Coronary artery disease patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Elevated PMV levels were associated with glycaemic profiles and amplified thrombotic tendencies [ 65 ]. Similar observations were reported by Bratseth and colleagues, highlighting elevated PMV levels in coronary artery disease patients with type 2 diabetes and albuminuria as potential predictors of disease severity [ 66 ]. In a project investigating the influence of PMVs in early diabetic nephropathy Zhang et al revealed that PMVs induce the production of reactive oxygen species (ROS), decrease nitric oxide levels and promote barrier permeability in glomerular endothelial cells.…”
Section: Immune-modulatory Function Of Plateletssupporting
confidence: 88%
“…Elevated PMV levels were associated with glycaemic profiles and amplified thrombotic tendencies [ 65 ]. Similar observations were reported by Bratseth and colleagues, highlighting elevated PMV levels in coronary artery disease patients with type 2 diabetes and albuminuria as potential predictors of disease severity [ 66 ]. In a project investigating the influence of PMVs in early diabetic nephropathy Zhang et al revealed that PMVs induce the production of reactive oxygen species (ROS), decrease nitric oxide levels and promote barrier permeability in glomerular endothelial cells.…”
Section: Immune-modulatory Function Of Plateletssupporting
confidence: 88%
“…Also, some cMVs expose phosphatidylserine (PS) at the outer leaflet during their biogenesis, conferring procoagulant activity, thus promoting the development and progression of atherothrombosis (Suades, Padro, Vilahur, & Badimon, 2012). High levels of cMVs have been related to the severity of acute myocardial infarction, both in patients with diabetes or coronary heart disease (Bratseth et al, 2019;Suades et al, 2012). Due to their molecular load, cMVs seem to contribute both to the onset and progression of vascular disease and also to participate in the occurrence of clinical events (Ridger et al, 2017).…”
mentioning
confidence: 99%
“…T2DM patients obtained benefits of physical training too. T2DM patients with coronary artery disease, albuminuria, and microalbuminuria had higher levels of circulating endothelial related EVs, monocyte-derived EVs, platelet-derived Evs, and EVs from endothelial progenitor cells (EPCs) [ 235 ]. Increased circulating EVs from endothelial cells indicate vascular injury progression, atherosclerosis, and nephropathy [ 124 , 236 , 237 , 238 ].…”
Section: Unraveling Underlying Mechanisms: Therapeutical Approachesmentioning
confidence: 99%